From waste to green applications: the use of recovered gold and palladium in catalysis - McCarthy,S; Lee,Wei Jie A; Braddock,D; Serpe,A; Wilton-Ely,J (Molecules, 2021)
The direct use in catalysis of precious metal recovery products from industrial and consumer waste is a very promising recent area of investigation. It represents a more sustainable, environmentally benign, and profitable way of managing the low abundance of precious metals, as well as encouraging new ways of exploiting their catalytic properties. This review demonstrates the feasibility and sustainability of this innovative approach, inspired by circular economy models, and aims to stimulate further research and industrial processes based on the valorisation of secondary resources of these raw materials. The overview of the use of recovered gold and palladium in catalytic processes will be complemented by critical appraisal of the recovery and reuse approaches that have been proposed.